On the Shoulders of Giants: Tracing Back the Intellectual Sources of the Current Debate on “GDP and Beyond” to the 19th Century - Nils aus dem Moore; Christoph M. Schmidt (Jahrbücher für Nationalökonomie und Statistik, 2013)
An eternal motive of human existence is the search for guidance.While values and beliefs retain their high relevance, today's enlightened societies also tend to rest their aspirations and decisions on the actual facts and on a sober assessment of possible courses of events emerging from different choices. Given the complexity of modern life, it is by now well understood that this strategy requires objective, comprehensive and accessible statistical reporting. Today, the desire to provide such a valuable basis for individual decisions and policy-making finds one of its most important expressions in the international debate on “GDP and beyond”. In contrast to similar efforts displayed in previous decades, the current projects emphasize sustainability issues and focus on the accessibility of the information, using modern tools of measurement and presentation. Yet, there is ample evidence that even by the mid-19th century economists aspired to use the objectifying power of statistical analysis as an instrument to improve policy-making and to achieve societal progress. Many of the approaches entertained today have thus to be viewed as an extension of attempts started at that time.
Keywords: 330; GDP; well-being; quality of life; sustainability; indicator systems